(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Infant and young child feeding practices have substantial consequences for the growth, development, and survival of infants and children during the first two years of life and throughout life. The study aimed to assess the infant and young child feeding practices among the caregiver of children (0 -23 months) enrolled in a community infant and young child feeding programme. A validated semi-structured questionnaire was used to collect informations. The major food consumed was legumes (62.7%) and cereals (60.8%). Over (74.8%) of the caregivers were still breastfeeding during the period of the study, (22%) of caregivers initiated breastfeeding within one hour of birth and 8.2% exclusively breastfed their children; the majority (91.7%) of the caregivers breastfed on demand. Only (24.5%) of the caregiver met minimum meal frequencies, (10.1%) diversified their diet, while (47.5%) met the minimum acceptable diet. Almost two third of the indices measured for the quality of Communit Infant and Young Child Feeding programme was rated very good in Wucicciri , rated poor in Rafin Magaji and also poor in Babban Dodo primary health care. This study revealed inappropriate infant and young child feeding practices in study area, despite being enrolled in the Communit Infant and Young Child Feeding programme. Therefore, these poor practices needed urgent action and aggressive sustained intervention.